2023
DOI: 10.1101/2023.01.20.524596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine D2 receptors in nucleus accumbens cholinergic interneurons increase impulsive choice

Abstract: Impulsive choice, often characterized by excessive preference for small, short-term rewards over larger, long-term rewards, is a prominent feature of substance use and other neuropsychiatric disorders. The neural mechanisms underlying impulsive choice are not well understood, but growing evidence implicates nucleus accumbens (NAc) dopamine and its actions on dopamine D2 receptors (D2Rs). Because several NAc cell types and afferents express D2Rs, it has been difficult to determine the specific neural mechanisms… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that the inactivation of the orbitofrontal cortex 28 and the nucleus accumbens 4 produces different effects on delay discounting depending on the basal levels of impulsivity, and suggested that low and high impulsivity have different neurobiological substrates 52 . In support of this idea, evidence shows that a higher number of D2 dopamine receptors in the mPFC 42 and the nucleus accumbens 45 is associated with low and high impulsivity, respectively. Furthermore, a very recent study shows that basal impulsivity is associated with the activity of mPFC-nucleus accumbens projections 32 .…”
Section: Discusionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that the inactivation of the orbitofrontal cortex 28 and the nucleus accumbens 4 produces different effects on delay discounting depending on the basal levels of impulsivity, and suggested that low and high impulsivity have different neurobiological substrates 52 . In support of this idea, evidence shows that a higher number of D2 dopamine receptors in the mPFC 42 and the nucleus accumbens 45 is associated with low and high impulsivity, respectively. Furthermore, a very recent study shows that basal impulsivity is associated with the activity of mPFC-nucleus accumbens projections 32 .…”
Section: Discusionmentioning
confidence: 88%
“…Moreover, ISD did not change accuracy or choice latency, which indicates that ISD does not produce general alterations in cognitive (i.e., attention, working memory) or motor (i.e., motor impulsivity) behavior. The effects of ISD increasing delay discounting could be related to alterations in time processing (i.e., increase delay intolerance) or due to alterations in the subjective value of rewards, giving more value to immediate rewards in a context of higher uncertainty 43,[45][46][47] .…”
Section: Discusionmentioning
confidence: 99%